Electrospinning Processing Techniques for the Manufacturing of Composite Dielectric Elastomer Fibers - Mirella Ramirez (MDPI AG, 2021)
Dielectric elastomers (DE) are novel composite architectures capable of large actuation strains and the ability to be formed into a variety of actuator configurations. However, the high voltage requirement of DE actuators limits their applications for a variety of applications. Fiber actuators composed of DE fibers are particularly attractive as they can be formed into artificial muscle architectures. The interest in manufacturing micro or nanoscale DE fibers is increasing due to the possible applications in tissue engineering, filtration, drug delivery, catalysis, protective textiles, and sensors. Drawing, self-assembly, template-direct synthesis, and electrospinning processing have been explored to manufacture these fibers. Electrospinning has been proposed because of its ability to produce sub-mm diameter size fibers. In this paper, we investigate the impact of electrospinning parameters on the production of composite dielectric elastomer fibers. In an electrospinning setup, an electrostatic field is applied to a viscous polymer solution at an electrode’s tip. The polymer composite with carbon black and carbon nanotubes is expelled and accelerated towards a collector. Factors that are considered in this study include polymer concentration, solution viscosity, flow rate, electric field intensity, and the distance to the collector.